2010
DOI: 10.1016/j.freeradbiomed.2009.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and glutathione in TGF-β-mediated fibrogenesis

Abstract: Transforming growth factor beta (TGF-β) is the most potent and ubiquitous profibrogenic cytokine and its expression is increased in almost all the fibrotic diseases and in experimental fibrosis models. TGF-β increases ROS production and decreases the concentration of glutathione (GSH), the most abundant intracellular free thiol and an important antioxidant, in various types of cells, which mediates many of TGF-β’s fibrogenic effects. A decreased GSH concentration is also observed in human fibrotic diseases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
338
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(359 citation statements)
references
References 331 publications
(250 reference statements)
10
338
0
4
Order By: Relevance
“…Previous reports have showed that ROS can regulate TGF-β1 synthesis GONZÁLEZ-RAMOS ET AL. 4 (5,12,17,23,25,32) also through the activation of the transcription factor AP-1 (12). Taking into account this fact, we hypothesized that basal concentrations of ROS could be involved in the constitutive expression of TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have showed that ROS can regulate TGF-β1 synthesis GONZÁLEZ-RAMOS ET AL. 4 (5,12,17,23,25,32) also through the activation of the transcription factor AP-1 (12). Taking into account this fact, we hypothesized that basal concentrations of ROS could be involved in the constitutive expression of TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β is the most extensively studied molecule in fibrosis and stimulates the production of reactive oxygen species (ROS) in various types of cells, whereas ROS activated TGF-β and mediate many of the fibrogenic effects of TGF-β [22]. TGF-β1 is known to induce fibroblast differentiation of into myofibroblast/smooth muscle cell in the human prostate [23].…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Various cytokines and growth factors are involved in the development of fibrosis; however, TGF-␤ is considered to be the most potent and ubiquitous profibrogenic cytokine. 25 TGF-␤ induces fibrosis via the stimulation of fibroblast proliferation and activation. 26 TGF-␤ also upregulates the expression of extracellular matrix (ECM) proteins, which leads to increased ECM production and reduced ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ increase ROS production in numerous types of nonphagocytic cells, such as endothelial cells, epithelial cells, smooth muscle cells, and fibroblasts. 25,27,28 In addition to stimulating ROS production directly, TGF-␤ increases ROS levels by suppressing the expression of several antioxidant enzymes. 25,29 ROS also activates latent TGF-␤ and induces TGF-␤ gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation